Pelaksanaan Tanggung Jawab Sosial Perusahaan Melalui Program Pemulihan Mata Pencaharian Oleh Lembaga X - Ridho, Muhammad Hanif; Maulana, Mochammad Rizqy; Nasri, Muhamad Azami (UI Scholars Hub, 2023)
This study examines the implementation of corporate social responsibility through the Livelihood Restoration Program (LRP) by Institution X. The study employs a qualitative approach with descriptive research methodology. Data collection techniques include in-depth interviews and literature review. The study is motivated by land acquisition conducted by PT Y, which affected the livelihoods of the local community. Consequently, PT Y initiated livelihood restoration for the affected community through the LRP managed by Institution X. The findings indicate that Institution X has two primary roles: providing consultancy services and facilitating the implementation of the LRP. First, as a consultancy agency, Institution X offers inputs and recommendations to PT Y, including steps and strategies for managing the affected community's livelihoods. Second, in facilitating the LRP, Institution X undertakes several stages, starting with (a) the preparation stage, which involves team formation, validation of assessment reports, and planning design during the accompaniment period, institution establishment, and outcome evaluation processes; (b) the validation (assessment) stage, where Institution X deploys social experts and planners to assess the community's livelihood conditions; (c) the implementation stage, where Institution X focuses on developing local potentials and the economic conditions of Project Affected Persons (PAPs) through interventions such as training and entrepreneurship awareness; (d) the reporting stage, where Institution X prepares reports as an accountability measure for the LRP implementation to PT Y; and (e) the evaluation stage, where Institution X measures the success of the LRP's planning and implementation for the affected community.